2015
DOI: 10.1016/j.jaac.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Moderators of Child- and Family-Focused Cognitive-Behavioral Therapy for Pediatric Bipolar Disorder

Abstract: Objective-Prior work has demonstrated the efficacy of child-and family-focused cognitivebehavioral therapy (CFF-CBT) versus enhanced treatment as usual (TAU; unstructured psychotherapy) for pediatric bipolar disorder (PBD). The current study builds on primary findings by examining baseline child, parent, and family characteristics as moderators of symptom response trajectories.Method-Sixty-nine youth ages 7-13 (M = 9.19, SD = 1.61) with DSM-IV-TR bipolar I, II, or not otherwise specified (NOS) were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Such parent and family variables have also been found to predict and moderate treatment effects. While more impaired children and families tend to benefit most from EBTs for BPSD (MacPherson et al, 2014; Miklowitz et al, 2009; Weinstein et al, 2015) and disruptive behavior (Gardner, Hutchings, Bywater, & Whitaker, 2010), caregiver stress is generally predictive of worse treatment outcomes for anxiety (Compton et al, 2014; Crawford & Manassis, 2001), though treatments with active parental involvement are highly effective for anxious children (Manassis et al, 2014). Thus, families of children with anxiety, disruptive behavior, or especially BPSD, experience considerable stress and may require more structured and intensive interventions with high levels of parental involvement to experience benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such parent and family variables have also been found to predict and moderate treatment effects. While more impaired children and families tend to benefit most from EBTs for BPSD (MacPherson et al, 2014; Miklowitz et al, 2009; Weinstein et al, 2015) and disruptive behavior (Gardner, Hutchings, Bywater, & Whitaker, 2010), caregiver stress is generally predictive of worse treatment outcomes for anxiety (Compton et al, 2014; Crawford & Manassis, 2001), though treatments with active parental involvement are highly effective for anxious children (Manassis et al, 2014). Thus, families of children with anxiety, disruptive behavior, or especially BPSD, experience considerable stress and may require more structured and intensive interventions with high levels of parental involvement to experience benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while poor child functioning has been implicated as a treatment moderator for pediatric BPSD (MacPherson, Algorta, Mendenhall, Fields, & Fristad, 2014), parent and family variables also moderate treatment outcomes. Specifically, moderators include elevated parent depression (Weinstein, Henry, Katz, Peters, & West, 2015), low income (Weinstein et al, 2015), elevated negative expressed emotion (Miklowitz et al, 2009), and increased conflict (Sullivan et al, 2012), with more impaired children and families generally benefitting most from EBTs for BPSD. Finally, parent and family constructs can mediate improvements in child mood symptoms and functioning in response to EBTs.…”
Section: Parenting Stress Among Caregivers Of Children With Psychiatrmentioning
confidence: 99%
“…Moderator analyses indicated that CFF-CBT was most impactful for parents with severe depression and low income, and families with high cohesion (Weinstein, Henry, Katz, Peters, & West, 2015). In addition, children with milder depression and greater self-confidence fared more poorly in TAU.…”
Section: Introductionmentioning
confidence: 99%
“…Rainbow integrates individual CBT with family psychoeducation and mindfulness skills sessions. In a second article, using the same cohort as the West et al study, Weinstein et al 7 examined baseline child, parent and family variables as potential moderators of response to CFF-CBT or a treatment-as-usual (TAU) comparison group.
Elements of the RAINBOW Programme6 7

R= R outines (developing consistent daily habits)

A= A ffect Regulation

I= I can do it!

…”
Section: Selected Studiesmentioning
confidence: 99%
“…For example, Beardslee et al 8 found that adolescents with a history of depression who participated in a group cognitive-behavioral therapy prevention programme had fewer onsets of depression over 33 months if mothers were not depressed at intake; those whose mothers had depression at baseline responded equally to the CBT prevention programme and the usual care comparator. In the West et al 6 paediatric bipolar trial, however, the interaction between parental depression, treatment and time is best understood as variability in the within-group symptom trajectories 7. Children responded similarly to CFF-CBT (ie, showed comparable levels of improvement in depression scores) independently of their parents’ levels of depression.…”
Section: Limitationsmentioning
confidence: 99%